Rifaximin anti‐inflammatory activity on bovine endometrium primary cell cultures: a preliminary study. Issue 4 (9th July 2018) - Flammini, Lisa; Mantelli, Leonardo; Volpe, Alessandra; Domenichini, Giuseppe; Di Lecce, Rosanna; Dondi, Maurizio; Cantoni, Anna Maria; Barocelli, Elisabetta; Quintavalla, Fausto
Abstract: Rifaximin is an unabsorbed oral antibiotic showing anti‐inflammatory properties in human pathologies like irritable bowel syndrome and inflammatory bowel disease. In veterinary medicine, rifaximin is primarily used in the treatment of dermatological diseases in all animal species, in therapy and prophylaxis of mastitis in cows and in the treatment of endometritis in cattle and horses. The aim of this preliminary study was to evaluate the anti‐inflammatory properties of rifaximin on primary cell cultures from bovine endometrium in which inflammatory response was induced by Lipopolysaccaride (LPS) treatment. Epithelial and stromal cells were isolated from bovine endometrium and separately incubated for 24 h with 1  μ g mL −1 LPS after rifaximin (10, 50 and 100  μ mol L −1 ) or dexamethasone (10  μ mol L −1 ) pre‐treatment for 24 h. Supernatants were collected 24 h after LPS treatment and interleukin (IL)‐6 and IL‐8 accumulation was measured by ELISA. Rifaximin (10, 50 and 100  μ mol L −1 ) dose dependently inhibited the LPS‐induced increase in IL‐6 and IL‐8 in stromal cells, whereas in epithelial cells it was not possible to detect any accumulation of these interleukins. Rifaximin reduced IL‐6 and IL‐8 production, showing a potential anti‐inflammatory effect that opens up to new possibilities for the use of this drug in uterine inflammatory diseases. Abstract : Rifaximin is an unabsorbed oral antibiotic that had shown also anti‐inflammatory properties in human pathologies. It is used in veterinary medicine as antibacterial in mastitis and endometritis in cattle but its antiflogistic activity in cows remains unknown. In this work, we report rifaximin ability to reverse LPS‐induced IL‐6 and IL‐8 production in bovine stromal endometrium cells. The present findings provide the first evidence of a potential anti‐inflammatory activity of rifaximin in cow endometritis.